Multiple Group Structural Equation Modeling of the Social Relations Model. Issue 5 (3rd September 2022) - Jendryczko, David
Abstract: The social relations model is a statistical tool that allows the analysis of group dynamics as dyadic interactions between individuals. Within a multiple group structural equation modeling framework, Wald-tests and likelihood ratio tests based on (1) equality constraints among model parameters and (2) Lagrange multipliers for restrictions among non-linear parameter transformations are presented as methods for group-comparisons of various quantifications of group dynamics that hold different interpretations. The methods are illustrated with an empirical example. A simulation study investigates the performance of the methods with regard to Type I error-rate recoverability and statistical power and displays overall promising results. Implications and limitations are discussed.